A Rare Cause of Oligohydramnios: A Case Report - Nadia Ben Jamaa; Radhouane Achour; Imen KSIBI; Mohamed Tahar Yacoubi; Sihem Hmissa; Moncef Mokni (Global Journal of Rare Diseases - Peertechz Publications, 2016)
Anamnios is due to extrinsic and intrinsic conditions. Intrinsic causes include maternal and fetal abnormalities mostly due to cystic renal changes or absence of kidney. Tubular dysgenesis characterized by a lack of proximal tubules should be considered. We report a case of tubular dysgenesis associated with lack of vault ossification in the fetus of a 23 year-old woman, prim pare, having a second degree of consanguinity. Ultrasonographic examination performed at 20 weeks of pregnancy identified severe anamnios. Few days later, intrauterine fetal death occurred. The complete autopsy with fetal radiography was performed. The external examination shows a hypotrophic male fetus with oligoamnios sequence deformation and a loss of vault ossification in the skeletal radiography. At dissection, we noticed a pulmonary hypoplasia with small kidneys, having normal architecture at cutting. The histological examination of the samples taken from the kidney shows a hypoplastic feature with a preserved architecture, a conserved cortico-medullary differentiation and the presence of rows of immature nephron at the edges; a very prominent reduction of proximal tubules is noticed. The immunohistochemistry showed a positivity of the tubules with EMA. However, there was lack of positivity with liposomes and alpha anti-trypsine. The diagnosis of tubular dysgenesis associated with lack of vault ossification was retained. Even the kidneys grossly seem to be normal, microscopic study should be meticulous in order to detect segmental nephronic anomalies as tubular dysgenesis. The examination of the bone mineralization and other organs as the liver can sometimes classify this kidney dysgenesis in rare syndromic anomalies.